The correlation between scoliosis and nutritional status among junior high school students in Shanghai city in 2022 - Wenjuan QI; Fengyun ZHANG; Yanting YANG; Liting CHU; Yuting HUANG; Shenglei HUANG; Keyang ZHENG; Dongling YANG; Chunyan LUO (Zhongguo gonggong weisheng)
ObjectiveTo investigate the association between scoliosis and nutritional status among junior high school students in Shanghai city and to provide a basis for the prevention and control of scoliosis in children and adolescents. MethodsFrom September to October 2022, a multi-stage stratified cluster sampling method was used to select 10 710 junior high school students from 16 districts in Shanghai city for scoliosis screening, anthropometric measurements, and questionnaire surveys. A two-level ordered multi-categorical logistic regression analysis was used to analyze the association between scoliosis and nutritional status. ResultsThe positive rate of scoliosis screening among junior high school students in Shanghai city was 1.93%, and the positive rate of poor posture was 4.04%. The positive rate of scoliosis in girls (2.70%) was higher than that in boys (1.22%) (χ2=32.217, P<0.001). The positive rate of scoliosis increased with grade (χ2=12.689, P<0.001). The positive rate of scoliosis in students from economically better-off areas (2.27%) was higher than that in students from moderately (1.66%) and less well-off areas (1.67%) (χ2=55.092, P<0.001). Univariate analysis found that moderately and severely underweight boys (OR=2.478, 95%CI: 1.316–4.665) had a higher risk of scoliosis than students of normal weight, and the same was true for girls (OR=2.455, 95%CI: 1.302–4.630). Among boys, overweight (OR=0.526, 95%CI: 0.371–0.746) and obese (OR= 0.472, 95%CI: 0.334–0.667) students had a lower risk of scoliosis than students of normal weight. Among girls, only obese students (OR=0.572, 95%CI: 0.380–0.861) had a lower risk of scoliosis than students of normal weight. After adjusting for confounding factors such as grade, economic status of the area, maternal education level, reading and writing posture, mobile electronic device usage time, sedentary time, frequency of desk and chair adjustment, and frequency of left and right seat adjustment, the two-level ordered multi-categorical logistic regression analysis showed that moderately and severely underweight boys (OR=2.442, 95%CI: 1.282–4.651) and girls (OR=2.495, 95%CI: 1.315–4.732) still had a higher risk of scoliosis than students of normal weight. Overweight (OR=0.522, 95%CI: 0.367–0.743) and obese boys (OR=0.481, 95%CI: 0.339–0.682) had a lower risk of scoliosis than normal-weight boys, and obese girls (OR=0.544, 95%CI: 0.362–0.822) had a lower risk of scoliosis than normal-weight girls. ConclusionsJunior high school students in Shanghai with low body weight have a high risk of scoliosis, while those with high body weight have a low risk of scoliosis. It is necessary to pay close attention to the risk of scoliosis in underweight students to achieve early screening, early detection, and early intervention.